INFLUENCE OF FLOODING ON LEAF CELL MEMBRANES OF THREE LATVIAN WHEAT CULTIVARS (TRITICUM AESTIVUM (L)). (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Flooding occurs in many wheat-growing regions around the world. During flooding, the gas exchange between soil and air decreases and root hypoxia or anoxia is the major cause of plant growth reduction under this stress. The hypoxia stress triggers stimulate the formation of reactive oxygen species (ROS) and induce oxidative stress in plants. The wheat is one of the most important crops in Latvia and in the world. Although wheat is one of the most intolerant crops to soil flooding. To elucidate the mechanisms involved in soil flooding and the tolerance of three Latvian commercial winter wheat (Triticum aestivum L.) cultivars: ‘Fredis’, ‘Reinis’, ‘Brencis’ and the flooding induced changes in electrolyte leakage, MDA production, and carotenoid production evaluated. The results indicate, that content of MDA, which reflect the level of membrane lipid peroxidation, differ, but no significant decrease of MDA concentration in cultivar ‘Brencis’ caused by increased activity of the antioxidant system. The differences in total carotenoids content in investigated wheat cultivars under simulating natural flooding founded. The most active accumulation of total carotenoids observed in the cultivar ‘Reinis’. The results demonstrate increased electrolyte leakage in cell membranes of the first leaves in all investigated wheat cultivars compared to control. Under flooding, the first leaf of wheat influenced by lower water temperature compared to the first leaf of the control group and that decrease the membrane fluidity, which possibly leads to decreased of membrane permeability. This preliminary data shows that one-week flooding influences to the cell membranes of some Latvian winter wheat cultivars, this influence differs, but cultivar ‘Brencis’ was more tolerant of the flooding.